The Extent to Which Obesity and Population Nutrition Are Considered by Institutional Investors Engaged in Responsible Investment in Australia - A Review of Policies and Commitments - Robinson, Ella; Parker, Christine; Carey, Rachel; Sacks, Gary (Frontiers in Psychology, 2020)
Introduction: Responsible investment (RI), in which environmental, social and governance (ESG) considerations are incorporated into investment decision making, is a potentially powerful tool for increasing corporate accountability and improving corporate practices to address broad societal and stakeholder interests. Whilst the RI sector is growing, there is limited understanding of the extent to which pressing social issues, such as obesity and unhealthy population diets, are incorporated within RI decision making. This study aimed to investigate the extent to which obesity prevention and population nutrition are considered by Australian institutional investors engaged in responsible investment. Methods: A desk-based review was conducted of investment approaches of prominent Australian asset managers and superannuation funds identified as engaged in responsible investment. Relevant information on the incorporation of ESG issues related to obesity and population nutrition was extracted for each investor, drawing on websites, published policy documents and annual reports. Strategies were categorised as: 1) negative/exclusionary screening; 2) positive/best-in-class screening; 3) norms-based screening; 4) ESG integration; 5) sustainability-themed investing; 6) impact/community investing; and 7) corporate engagement and shareholder action. These strategies were compared across investors and by themes related to obesity and population nutrition. Results: Eighteen of the 35 investors indicated that they applied investment strategies that considered issues related to obesity and population nutrition. The most commonly identified strategy was ESG integration (n=12), followed by sustainability-themed investing (n=6), and positive screening (n=4). The ways in which obesity and population nutrition were considered as part of these approaches included relatively high-level general health considerations (n=12), considerations around the healthiness of food company product portfolios (n=10), and consideration of specific company nutrition policies and practices (n=4). The specificity and depth to which RI strategies were disclosed varied. Conclusions: There is significant potential for investment decisions to contribute to efforts to address key social issues, such as obesity and unhealthy diets. Some institutional investors in Australia have recognised the potential importance of incorporating obesity- and population nutrition-related issues into decision-making processes. However, the extent to which these considerations translate into investment decisions and their impact on companies in the food sector warrant further exploration.